2018
DOI: 10.1002/jcb.26742
|View full text |Cite
|
Sign up to set email alerts
|

Jolkinolide B inhibits glycolysis by downregulating hexokinase 2 expression through inactivating the Akt/mTOR pathway in non‐small cell lung cancer cells

Abstract: Jolkinolide B (JB), a bioactive compound isolated from herbal medicine, has been found to inhibit tumor growth by altering glycolysis. However, whether glycolysis is influenced by JB in non-small cell lung cancer (NSCLC) cells and the mechanism remain unknown. The aim of the present study was to evaluate the effect of JB on the glycolysis in NSCLC cells and the underlying molecular mechanism. The results showed that JB treatment inhibited cell viability of A549 and H1299 cells in a concentration-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Interestingly, a number of naturally occurring compounds have been found to modulate glycolysis by regulating HK2. For instance, a recent report by Gao et al has shown that jolkinolide B (JB), a bioactive compound isolated from the medicinal Euphorbia fischeriana Steud plant, inhibits glycolysis by suppressing HK2 expression in non‐small cell lung cancer cells . Curcumin has also been found to inhibit glycolysis by inducing dissociation of HK2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a number of naturally occurring compounds have been found to modulate glycolysis by regulating HK2. For instance, a recent report by Gao et al has shown that jolkinolide B (JB), a bioactive compound isolated from the medicinal Euphorbia fischeriana Steud plant, inhibits glycolysis by suppressing HK2 expression in non‐small cell lung cancer cells . Curcumin has also been found to inhibit glycolysis by inducing dissociation of HK2 .…”
Section: Discussionmentioning
confidence: 99%
“…Because HK2 catalyzes the first committed and rate-limiting step in glucose metabolism by phosphorylating glucose, it is the most sought after target. 29 Interestingly, a number of naturally occurring compounds have been found to modulate glycolysis by regulating HK2. For instance, a recent report by Gao et al has shown that jolkinolide B (JB), a bioactive compound isolated from the medicinal Euphorbia fischeriana Steud plant, inhibits glycolysis by suppressing HK2 expression in non-small cell lung cancer cells.…”
Section: Euxanthone Suppresses Tumour Growth In a Xenograft Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding capacity of HK2 with VDAC1 diminished in a dose‐dependent manner by co‐immunoprecipitates analysis in cells treated with CTB (Figure E). Activated AKT plays a strong anti‐apoptotic role in tumour cells with high glycolysis rate, and the binding of HK2‐VDAC1 is regulated by upstream Akt . To assess whether CTB can affect the activation of the Akt signalling pathway, Western blot and immunofluorescence were used to determine the expression of p‐Akt and Akt.…”
Section: Resultsmentioning
confidence: 99%
“…Protein expression levels related to the PI3K/ mTOR signalling pathway are inhibited by both rapamycin and PI3K inhibitor in ex vivo organ culture Previous studies have shown that mTOR, including both mTORC1 and mTORC2, is downstream of the PI3K signalling pathway [2,3]. The PI3K inhibitor LY294002 has been used to investigate the function of mTOR signalling in various experiments [28,29]; therefore, we utilized this inhibitor to analsze mTOR related pathways in SMG development. We counted the number of branching buds in SMGs to clarify the Fig.…”
Section: Resultsmentioning
confidence: 99%